Basic characteristics of epileptiform discharges triggered by lindane in rats - Useinović, Nemanja G; Vorkapić, Marko; Leković, Aleksa; Ademović, Anida; Sutulović, Nikola; Grubač, Željko; Rašić Marković, Aleksandra; Hrnčić, Dragan; Stanojlović, Olivera (Medicinski podmladak, 2018)
Introduction: EEG is a widely used method of epilepsy examination. In order to quantitatively inspect ictal EEG findings, a number of mathematical models have been developed over the years, one of them being the Fast Fourier Transform (FFT). It transforms the signal from time domain into frequency domain, giving information about their power spectral densities (PSD). Lindane is a well-established neurotoxic agent often used in experimental studies as a model of generalized epilepsy. This study aims to quantitatively examine the characteristics of ictal EEG activity in rats on model of generalized epilepsy induced by lindane. Materials and Methods: Wistar albino rats were used for the study. Electrodes were surgically implanted over the frontal, parietal and occipital cortices of each animal for EEG recording purposes prior to lindane administration in convulsive dose. An 8-channel EEG apparatus was used, combined with a software developed in the Laboratory (NeuroSciLaBG). Ictal EEG epochs were extracted from the original signal and FFT analysis performed to obtain information considering PSD in predefined frequency bands. Amplitude histogram feature of the software was used to differentiate ictal spikes based on their voltage. Results: FFT analysis has yielded important information regarding spectral powers in frequency domain. Ictal EEG showed considerable stratification, theta frequency band (4-7 Hz) being markedly dominant. Amplitude histogram showed the majority of spikes to be in the voltage ranges up to 250 µV, while higher voltage spikes were rarely observed. Conclusion: FFT is capable of giving important information about ictal period characteristics. Ictal periods induced by lindane are characterized by dominancy of theta rhythm and spiking activity mostly in amplitude bins up to 250 µV.  FFT and amplitude histograms can be of critical importance in the future pharmacological and toxicity studies.   Keywords: seizures, EEG, FFT, lindane, rats